Adult bronchoscopy training: current state and suggestions for the future : CHEST expert panel report - Ernst, Armin; Wahidi, Momen M.; Read, Charles A.; Buckley, John D.; Addrizzo-Harris, Doreen J.; Shah, Pallav L.; Herth, Felix; de Hoyos Parra, Alberto; Ornelas, Joseph; Yarmus, Lonny; Silvestri, Gerard A. (Chest, 2015)
BACKGROUND - The determination of competency of trainees in programs performing bronchoscopy is quite variable. Some programs provide didactic lectures with hands-on supervision, other programs incorporate advanced simulation centers, whereas others have a checklist approach. Although no single method has been proven best, the variability alone suggests that outcomes are variable. Program directors and certifying bodies need guidance to create standards for training programs. Little well-developed literature on the topic exists. - METHODS - To provide credible and trustworthy guidance, rigorous methodology has been applied to create this bronchoscopy consensus training statement. All panelists were vetted and approved by the CHEST Guidelines Oversight Committee. Each topic group drafted questions in a PICO (population, intervention, comparator, outcome) format. MEDLINE data through PubMed and the Cochrane Library were systematically searched. Manual searches also supplemented the searches. All gathered references were screened for consideration based on inclusion criteria, and all statements were designated as an Ungraded Consensus-Based Statement. - RESULTS - We suggest that professional societies move from a volume-based certification system to skill acquisition and knowledge-based competency assessment for trainees. Bronchoscopy training programs should incorporate multiple tools, including simulation. We suggest that ongoing quality and process improvement systems be introduced and that certifying agencies move from a volume-based certification system to skill acquisition and knowledge-based competency assessment for trainees. We also suggest that assessment of skill maintenance and improvement in practice be evaluated regularly with ongoing quality and process improvement systems after initial skill acquisition. - CONCLUSIONS - The current methods used for bronchoscopy competency in training programs are variable. We suggest that professional societies and certifying agencies move from a volume-based certification system to a standardized skill acquisition and knowledge-based competency assessment for pulmonary and thoracic surgery trainees.